Funciones

Solo disponible en BuenasTareas
  • Páginas : 2 (387 palabras )
  • Descarga(s) : 0
  • Publicado : 20 de noviembre de 2010
Leer documento completo
Vista previa del texto
fx=ex

f1=e1
f1=2.72

f2=e2
f2=7.38

f3=e3
f3=20.08

x | y |
1 | 2.72 |
2 | 7.38 |
3 | 20.08 |

fx= 3+exf1=3+e1
f1=5.72

f2=3+e2
f2=10.38

f3=3+e3
f3=23.08

x | y |
1 | 5.72 |
2 | 10.38 |
3 | 23.08 |

fx=2+e(x+1)

x+2=0
x=-2y-1=6+ln⁡(-1+2)
y-1=6+ln⁡(1)
y-1=6
y0=6+ln⁡(0+2)
y0=6+ln(2)
y0=6.69
y1=6+ln(1+2)
y1=6+ ln(3)
y1=7.09
x | y |
1 | 6 |
2| 6.69 |
3 | 7.09 |

fx= 2+e(x-1)

x+3=0
x=-3
y-2=-4+ln(-2+3)
y-2=-4+ln⁡(1)
y-2=-4
y-1=-4+ln⁡(-1+3)
y-1=-4+ln(2)
y-1=-3.30y0=-4+ln(0+3)
y0=-2.90

x | y |
1 | -4 |
2 | -3.3 |
3 | -2.9 |

fx= 7+e(x+2)

x-5=0
x=5
y6=3+ln(6-5)
y6=3+ln⁡(1)y6=3
y7=3+ln⁡(7-5)
y7=3+ln(2)
y7=3.69
y8=3+ln(8-5)
y8=3+ln(3)
y8=4.09
x | y |
1 | 3 |
2 | 3.69 |
3 | 4.09 |

fx=5+e(x+2)x-2=0
x=2
y3=-2+ln(3-2)
y3=-2+ ln⁡(1)
y3= -2
y4=-2+ln⁡(4-2)
y4=-2+ln(2)
y4=-1.31
y5=-2+ln(5-2)
y5=-2+ln⁡(3)
y5=-0.91
x| y |
1 | 2 |
2 | -1.31 |
3 | -0.91 |

fx= e(3x-1)

x3-2=0
x=32
x=1.25
y2=ln(23-2)
y2=ln⁡(6)
y2=1.79
y3=ln⁡(33-2)y3=ln(25)
y3=3.21
y4=ln(43-2)
y4=ln(62)
y4=4.12
x | y |
1 | 0 |
2 | 0.69 |
3 | 1.09 |

fx= 1+e(x+1)

2x-4=0
x=2y3=ln(2(3)-4)
y3=ln⁡(2)
y3=0.69
y4=ln⁡(2(4)-4)
y4=ln(4)
y4=1.38
y5=ln25-4
y5=1.79

x | y |
1 | 0.69 |
2 | 1.38 |
3 | 1.79 |
tracking img